Pendugaan Intensitas Serangan Penyakit Blas pada Tanaman Padi Melalui Pendekatan Citra NDVI (Normalized Difference Vegetation Index) - I Made Prasetia Candra Andika; I Made Anom S. Wijaya; Ida Bagus Putu Gunadnya (Program Studi Teknik Pertanian dan Biosistem, Fakultas Teknologi Pertanian, Universitas Udayana, Badung, Bali, Indonesia, 2019)
Blast is one of disease that is dangerous for rice plants. This disease can attack in every phase of growth. Calculation of the intensity of blast disease attacks is still done manually. Technology development is needed in estimating the intensity of blast disease attacks through NDVI imagery. This study purpose (1) to get the best NDVI aerial photo altitude, (2) to get the age of rice plants with the highest attack intensity of blast disease, (3) to get a relationship between the intensity of blast disease and the NDVI value of rice plants. This study use Drone DJI Phantom 4 with lens NDVI. Processing data using Web Drone Deploying and Arc Gis 10.3 software. Based on the analysis results, the best detail of 200% zooming results obtained altitude of the NDVI image acquisition that is 20 m with pixel density of 1,4732 cm/pixel. The highest intensity of blast disease attacks occurs at the age of 98 days after planting. The relationship between the intensity of blast disease and NDVI value has a determination coefficient of 0.986. The regression equation obtained in this study is y = -23345x3+ 21191x2-6416,8x + 665,07 with an estimated accuracy of 91,74%